PENGARUH WAKTU EKUILIBRASI TERHADAP KUALITAS SEMEN BEKU BABI LANDRACE DALAM PENGENCER DURASPERM TERMODIFIKASI (Effect of equilibration time on the quality of landrace boar frozen semen in modified durasperm extender) - Sofia Marlize; Thomas M. Hine; Wilmientje M. Nalley (Universitas Nusa Cendana, 2021)
This study aims to determine the effect of equilibration time on the quality of landrace spermatozoa both pre- and post-freezing and to find the best equilibration time. The materials used is fresh semen collected from a 2,5 years old landrace boar. Collecting was carried out twice per week using the glove hand method. Semen of good quality (sperm motility ≥70%, sperm concentration ≥200 x 106 cells/ml, and percentage of sperm abnormalities ≤15%) was diluted with durasperm that had been modified with lontar fruit juice, while the cryoprotectants used glycerol and sucrose. Holding time was carried out for 2 hour at 27-28°C, centrifuged at 2000 rpm for 15 minutes, and the sperm sediment was diluted with the same diluent. After that, the liquid semen was packed in a 0.5 mL straw and equilibrated at 3-5°C for 1 (P1), 2 (P2), or 3 hours (P3). The freezing of semen was carried out on the surface of liquid nitrogen at a distance of 5 cm for 10 minutes, and then stored in a liquid nitrogen container. Thawing is done by placing the frozen semen straws in warm water (37°C) for 30 seconds. The research data were analyzed with analysis of variance and continued with the Duncan test. The results showed that the equilibration time at 2 hours (P2) gave the best results (P<0,05) with the mean percentage of motility, viability, abnormality, intact plasma membrane and recovery rate respectively were 30,62%, 58,21%, 4,68%, 58,94% and 43,74%. It was concluded that the equilibration time did not affect the quality of pre-freezing spermatozoa, but it did affect the quality of post-freezing spermatozoa with the best equilibration time to maintain the quality of frozen semen of landrace boar was 2 hours.